2006
DOI: 10.2214/ajr.04.1821
|View full text |Cite
|
Sign up to set email alerts
|

Inherent Variability of CT Lung Nodule Measurements In Vivo Using Semiautomated Volumetric Measurements

Abstract: Volumetric measurements show minimal interobserver variability (0.018%) but an interscan SEM of 13.1% (confidence limits, +/- 25.6%). Repeatability and reproducibility of volumetric measurements are better than those of linear measurements reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
94
3
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 18 publications
4
94
3
1
Order By: Relevance
“…The interscan standard deviation of the mean was 13.1 % (confidence limits, ± 25.6%), signaling the important and predominant influence of this factor on measurement reproducibility. In this study, the authors acknowledged that lung volumes were not controlled between scans, which may have contributed to the interscan variability they observed (22).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The interscan standard deviation of the mean was 13.1 % (confidence limits, ± 25.6%), signaling the important and predominant influence of this factor on measurement reproducibility. In this study, the authors acknowledged that lung volumes were not controlled between scans, which may have contributed to the interscan variability they observed (22).…”
Section: Discussionmentioning
confidence: 96%
“…In another recent study evaluating interobserver agreement (repeatability) and interscan agreement (reproducibility) of lung nodule volume measurements, Goodman et al used a fully automatic segmentation software program to compute the volumes of nodules scanned multiple times during the same session. The study was done on 50 nodules of less than 20 mm diameter (22). The authors reported a mean interobserver variability of 0.02% (SD = 0.73%), and concluded that interobserver variability was minimal (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Addressing the problem from a different perspective is the active interest in developing computer assisted methods that will aid the physician in measuring the size of lesions using volumetric methods [6][7][8][9][10][11]. The challenge here is how to calibrate and validate such methods.…”
Section: Introductionmentioning
confidence: 99%